Practices of Breast Self-Examination and Associated Factors among Female Debre Berhan University Students - Kalayu Birhane; Miskir Alemayehu; Belayneh Anawte; Gebru Gebremariyam; Ruth Daniel; Semeneh Addis; Teshome Worke; Abdurrahman Mohammed; Wassie Negash (International Journal of Breast Cancer)
Background. Breast cancer is the most prevalent form of cancer in Ethiopia of all female cancers. It is considered to be a progressive disease with a poor prognosis if detected late. Breast self-examination is an important prevention method of breast cancer. This study was aimed at assessing practice and associated factors of breast self-examination (BSE) among female Debre Berhan University students in Ethiopia. Methods. A cross-sectional study was conducted in 2015 among 420 using self-administrated questionnaire. Multistage sampling technique was used to select the study participants. Bivariate and multivariate logistic regression analysis were done. Results. Majority of the study participants, 338 (84.5%), were between 20 and 24 years old with the mean age of 21.1 ± 1.65. Only 14 (3.5%) had family history of breast cancer. Two hundred fifty-six (64%) of the participants had heard about BSE and 30.25% had good knowledge about BSE. Mass media were the most common source of information about breast cancer. Few of the participants (28.3%) had performed BSE. Lack of knowledge on how to perform BSE was cited as the main reason for not practicing BSE. Knowing how to perform, when to perform, and position to perform BSE and having a perception that BSE is important and useful to detect breast cancer were significant predictors of practices of BSE. Conclusions. This study revealed that most of the participants had low knowledge and practice of BSE. Therefore, it important to develop health educational programs in the university to raise awareness about BSE and breast cancer so as to practice self-breast examination.